Anatomy and specific variations in nasoethomoid region and their clinical significance - Bojadzieva Stojanoska, Biljana; Papazova, Marija; Korneti-Pekevska, Kostadina; Nakjeva Janevska, Natasha; Janevski, Petar (Macedonian Association of Anatomists and Morphologists, 2008)
The revolutionary changes in surgical treatment ment of paranasal sinuses in chronic sinusitis in the last twenty years, especially functional endoscopic sinus surgery (FESS), have increased the interest and necessity of clinicians for better understanding of the anatomy of sinonasal cavities and specific variations in this region. This article presents the anatomy and specific variations in the nasoethmoid region, evaluated on CT scans of paranasal sinuses, together with overview of literature. It also gives their clinical significance, for better understanding of sinus pathology, as well as easier diagnostic treatment and preoperative surgical planning in patients with chronic sinusitis.
Анатомски варијации во назоетмоидалното подрачје и нивното клиничко значење
Keywords: nasal cavity; paranasal sinuses; CT imaging